Modified pharmacy counseling improves outpatient short-term antibiotic compliance in Bali Province - I Gusti Ayu Rai Widowati; Dyah Pradnyaparamita Duarsa; Ni Nyoman Sri Budayanti; Ajeng Diantini; Pande Putu Januraga (International Journal of Public Health Science (IJPHS), 2022)
Pharmacy counseling, which provides quality drug information, improves patient safety. However, this service is not optimally provided in Indonesia. A new model, modified pharmacy counseling (MPC), was developed to make it easier for service providers. We aimed to measure MPC effectiveness in improving short-term antibiotic compliance. This community trial (ISRCTN82062391) involved patients (age, ≥18 years) recruited from selected pharmacies between December 2020 and February 2021 in two Bali Province districts. At baseline, data regarding sociodemographic characteristics, knowledge levels, and attitudes toward antibiotic use were collected. MPC effectiveness was assessed using Morisky medication adherence scale-8. Of 300 recruited patients, 290 participated (response rate, 96.67%). The baseline study revealed that knowledge regarding short-term antibiotic use is lacking; however, awareness regarding antimicrobial resistance is high. MPC significantly improved short-term antibiotic compliance (risk ratio, 2.849; 95% confidence interval, 1.904-6.640; p<0.001). The mean rank significantly differed between the intervention (61.05) and control groups (37.95). The proportions of compliant patients in the intervention and control groups were 35.6% and 12.5%, respectively. The main reason for low compliance was forgetting and not being made aware by pharmacy workers in the intervention (46.8%) and control (55.6%) groups, respectively. These findings provide insights for improving pharmaceutical care.